Design And Analysis Of Satellite's Ground Station - Yiap, Joo Zheng (Universiti Sains Malaysia, 2018)
Design and Analysis of Satellite’s Ground Station is a thesis project based on the development of the ground station for LEO satellite, MYSat, which is going to be launched by USM Space System Lab (USSL) in near future. The ground station consists of azimuth & elevation controller, terminal nodes controller (TNC), amplifier and pre-amplifier, rotator, a fabricated rotator-computer interface and VHF & UHF antennas that operated at dual frequencies which are 145.8 MHz and 437.45 MHz. This study investigated on the design and fabricated of rotator-computer interface, design of antennas with its supporting holder and design of ground station that includes visually integration between software and hardware. Rotator-computer interface is origin from Yaesu and is an open source device. An interface operated by Arduino Mega wasdesigned and fabricated in this study, which allows the connection to computer simply through USB port. Coding is uploaded to theinterface/Arduino that is compatible with GS232 command and allow the satellite tracking software to control both the azimuth and elevation rotators. The antenna was designed, and its performance was optimized and simulated using numerical electromagnetic code (NEC). At the end of the study, a complete ground station was designed to give vision on the integration between software and hardware, including the transmission lines used.